The effects of occupational pollutants on the reproductive health of female informal street traders in Warwick junction, Durban, South Africa – a cross-sectional study - Sujatha Hariparsad; Rajen N. Naidoo (BMC Women's Health, 2019)
Abstract Background Informal street traders are exposed on a daily basis to traffic emissions and biomass fuel smoke containing a variety of pollutants. These exposures are likely to place the female traders at increased risk for adverse reproductive outcomes. Aim The aim of this study was to compare the reproductive outcomes among street traders exposed to pollutants from their work-related activities and traders without such exposure. Methods A cross-sectional study was conducted among 305 female traders selected from exposed and non-exposed areas within the Warwick Junction trading hub, located in Durban, South Africa. Validated reproductive questionnaires and clinical assessments were conducted on all participants. Adverse reproductive outcomes such as low birth weight, spontaneous abortions and infertility were assessed. Results The mean age of the traders was 43.6 years (SD:12.1), mostly single (63%) and worked in trading hub for an average of 14 years. There were 876 pregnancies reported in the total sample. Traders pregnant while working in this location accounted for 120 pregnancies There was an increased risk of exposed traders having a low birth weight infant as compared to non-exposed traders (OR = 3.7; CI: 1.8, 7.6). Exposed traders were also almost 3 times more likely to be infertile as compared to non-exposed traders (OR = 2.6; CI: 1.6, 4.3). Conclusions This study has demonstrated that female street traders working within a trading hub in KwaZulu-Natal, South Africa; exposed to occupational pollutants show an association with developing infertility and low birth weight infants. Recommendations to mitigate adverse exposures have been suggested which include short term safety interventions and better cooking practices and future long term policy interventions.